Mendorong Ekspresi Diri Siswa Melalui Padlet: Cerminan Iklim Belajar yang Aman Tanpa Perundungan - I Putu Rama Putra Yasa; Luh Made Dwi Wedayanthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Bullying remains a critical issue in elementary school environments and significantly affects students’ social-emotional development. The lack of confidence among students to report negative experiences often results in bullying cases remaining undetected. This study aims to describe the implementation of Padlet as a reflective digital tool to encourage students’ self-expression and to analyze students’ reflections as indicators of a safe and supportive learning climate. This research employed a descriptive qualitative approach involving 14 sixth-grade students at SD Negeri 3 Demulih. Data were collected through reflective Padlet posts, activity documentation, and thematic deductive analysis based on the Aggression Continuum Theory. The findings reveal three categories of social interaction: (1) high-risk behaviors related to dominance and indicators of bullying, (2) medium-risk interactions involving verbal teasing normalization and ambiguous conflicts, and (3) low-risk interactions indicating positive peer relations and social needs. Padlet proved effective as a safe digital space for students to express emotional experiences anonymously and facilitated early identification of potential bullying. These results highlight the importance of utilizing reflective digital platforms to foster preventive, inclusive, and psychologically secure classroom environments.